POTENSI TRADISI BUDAYA MEGALITIK DI TANA TORAJA SEBAGAI OBJEK WISATA - Rosmawati Rosmawati (JURNAL ILMU BUDAYA, 2021)
Toraja cultural heritage, both in the form of cultural heritage and traditions that are still alive in society, are all manifestations of megalithic cultural traditions that have been known since the arrival of the influence of the Austronesian people to the present. Various forms of Toraja megalithic culture, such as menhirs (simbuang), burial forms (liang), settlements centred in Tonkonan, and various types of rituals that are still alive in the local community. The unique cultural wealth of Toraja, combined with beautiful natural conditions, has great potential to be managed and utilized for the tourism industry. Several cultural sites have been used as tourists objects, such as the Bori' Parinding megalith site, the Londa burial site, the Kete' Kesu settlement site, various traditional ceremonies in the life cycle of the Toraja people, and the daily life of the traditional Toraja people.